KINERJA KEUANGAN DAN RISIKO SISTEMATIS PERUSAHAAN MERGER - Kun Ismawati & Kim Budiwinarto (Universitas Slamet Riyadi, 2015)
Purpose of this research were to determine financial performance and systematical risk of the merged companies. This research based on social research. Purposes sampling used to identify the research samples in which related or unrelated characteristic. Hypothesis of this research tested by statistical method. There were two kinds of samples in this research: (1) companies with related merger; (2) companies with unrelated merger. The research results stated that; (1) there was a significant different in financial performance of the companies with related merger a year before merger and after 4 years merger; (2) there was a significant different in financial performance of the companies with unrelated merger a year before merger and after 4 years merger; (3) there was not a significant different in their financial performance between companies with related merger and unrelated merger; (4) there was a different systematical risk between companies with related merger and unrelated merger. Keywords: financial performance, systematical risk, merger